Influence of environmental features at multiple scales and spatial structure on stream fish communities in a tropical agricultural region - Roa-Fuentes, Camilo A. [UNESP]; Casatti, Lilian [UNESP] (Taylor & Francis Inc, 2017)
Land cover change for agricultural expansion exerts strong pressures on tropical streams. We examined the relative contributions of catchment land cover, local environmental features, and spatial patterns on stream fish communities (n = 43). Explained variation in fish community structure was partitioned (p-RDA) between the explained fractions as follows: pure local 10%, pure catchment 1%, pure spatial 3%, and shared environmental and spatial 7%. Among the possible reasons for the lack of effect of catchment-scale variables on stream fish structure we can cite (1) weak associations between catchment-scale and local-scale features that are affecting stream fish communities, (2) major influence of past land cover on the present-day fish community structure compared to current land cover, or (3) the small variability in catchment variables (e. g. homogeneous landscape) is not able to overcome the impact of localscale variables. The best practice to improve the ecological integrity of streams would be the restoration at the catchment-scale, which is impossible for agricultural lands. In areas with intense land use for agriculture and pasture, our study indicates that restoration of riparian forests and manipulation of local conditions may be an option to reduce the impacts of anthropogenic activities on the stream fish communities.
Keywords: Hierarchical classification; stream ecology; riparian cover; riparian width; reach-scale variables; Neotropical stream fish; agricultural landscape